Integrating Islamic Values Into Digital Learning for Character Education in Elementary Schools - Yusuf Yusuf; Ade Aspandi (Journal of Primary Education (JPE), 2026)
The rapid development of digital learning in elementary education has created new challenges in strengthening students’ character and moral values. Digital learning at the elementary school level often focuses more on cognitive achievement and technological adaptation, while the integration of religious and character values remains limited. This study aims to analyze the integration of Islamic values into digital learning as an effort to strengthen character education at SDN Taman Kalijaga Permai. The research employed a qualitative case study approach involving teachers, school principals, and elementary students as research participants. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the integration of Islamic values in digital learning is implemented through religious habituation before online learning activities, the insertion of Islamic messages in digital teaching materials, reflective learning activities, and teacher modeling in digital communication. The implementation of these strategies contributes positively to students’ discipline, responsibility, politeness, and digital ethics. However, several challenges remain, including limited teacher competence in value-based digital pedagogy and students’ inconsistent digital literacy levels. This study concludes that integrating Islamic values into digital learning can serve as an effective strategy for strengthening character education in elementary schools when supported by contextual learning approaches and active teacher involvement.